Energy prices and the economic feasibility of using hydrogen energy for road transport in the People's Republic of China - Yanfei Li; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2020)
This study develops quantitative models to conduct economic assessments of the feasibility of producing hydrogen energy from renewable energy and subsequently applying it in the road transport sector in the People's Republic of China. The study applies a well-to-wheel model to analyze the cost of hydrogen as storage for renewable energy, while it uses the total cost of ownership model to analyze the cost and carbon emissions of fuel cell vehicles' (FCEVs') mobility, using the hydrogen produced from renewables as fuel, in comparison with that of alternative vehicle powertrains, especially the conventional fossil fuel-based technology. On such a basis, the study discusses the relationship between the energy prices and the competitiveness of hydrogen produced from renewable energy as well as FCEVs.
Keywords: Q21; Q42; Q48; R48; 330; hydrogen; renewable energy; road transport; the People's Republic of China